(untitled) (World Science, 2023)
The principle of work of the thermal car assumes its interaction with environment according to thermodynamics laws. All real processes owing to a friction, heat exchange at a final difference of temperatures and limitation of time of their course are irreversible. As irreversibility measure entropy serves. The paper considers the peculiarities of the transformation of thermal energy, taking into account entropy. A theoretical analysis of the efficiency of work performance (exergy) is given. The equations of thermal and exergic balance of thermal engines are presented, taking into account the impact on the environment. The main parameters characterizing the loss of efficiency of the charge air during the period of filling the cylinder are determined and calculated: the filling factor and the loss of pump strokes. The calculated value of pumping losses allows, with sufficient for calculating the gas exchange of engines and especially for calculating the operation of pumping passages, to determine the amount of loss in the efficiency of air pre-compressed in the pressurization unit.